Eksperimen Pembelajaran Matematika Dengan Strategi Discovery Learning Dan Problem Based Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Kemampuan Koneksi Matematik Siswa Kelas VIII SMP N 1 Kartasura Tahun 2015/2016 - Saroh, Umay (2016)
ABTRACT UmaySaroh/A410120186 EXPERIMEN PEMBELAJARAN MATEMATIKA DENGAN STRATEGI DISCOVERY LEARNING DAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI KEMAMPUAN KONEKSI MATEMATIK SISWA KELAS VIII SMP N 1 KARTASURA TAHUN 2015/2016. Essay.Faculty of Teacher Training and Education.Muhammadiyah University of Surakarta. January, 2016 The aim of this research are to examine: (1) contribution of Discovery Learning (DL) and Problem Based Learning (PBL) strategies toward the result of the study in mathematic, (2) to examine the ability of students mathematic connection towards the result of mathematic study, (3) Interaction betwen learning strategy and mathematic connection towards the result of mathematic study. The type of this research is experimental method. The population in this research are all students in grade VIII of SMP N 1 Kartasura in 2015/2016 Academic Year. The research took two classes for samples. Those are experiment class that use DL strategy and control class that use PBL strategy . The tecknique of sampling is by using Simple Random Sampling. The data collection tecnique are using test and observation. In thi research, the researcher uses two way ANAVA with different cell in the data analysis tecnique. Before the snslysis test, the researcher did the normality test with Shapiro-Wilk test and homogenity tes is using F test. Based on the result of the research if